Entrepreneurial Practice in Trading on Javanese-Muslim Ethnicity and Chinese-Confucian Ethnicity in Kanoman Market, Cirebon City - Cahyono, Heru (Univeristas Islam Bandung, 2022)
In the practical realm, the market always provides room for contestation for the entrepreneurs involved in it. Likewise, in Kanoman Market, Cirebon City, this ethnic entrepreneurial contestation was represented by the two so-called ethnic groups, namely the Javanese-Muslim ethnicity and the Chinese-Confucian ethnicity. The contestation in the entrepreneurial field at Kanoman Market shows the dominance of confident entrepreneurs. For example, service entrepreneurs (corporate entrepreneurs) of Javanese ethnicity and entrepreneurs of essential commodities (trading entrepreneurs) are generally ethnic Chinese. The purpose of this study is to analyze the entrepreneurial contestation of Javanese-Muslim ethnicity and ethnic Chinese-Kunghucu at Kanoman Market, Cirebon. The research uses qualitative methods with an anthropological-economic approach. They are then equipped with data analysis to answer research questions. This study found that the entrepreneurial contestation of Javanese-Muslim and Chinese-Kunghucu ethnics in Kanoman Market, Cirebon City, the economic practices of the two ethnicities were carried out and shaped by the belief system of the community, whether influenced by the religious belief system adopted or the belief system sourced from ethnic values and the ethnic belief system. For this reason, in economic practice, especially in the contestation taking place in the market, the belief system forms its influence in accepting the Javanese-Muslim and Chinese-Kunghucu ethnicities on matters relating to the belief system they believe in. In their entrepreneurial practice, the two ethnic groups involve social capital and mystical capital, such as a network of associations and professional organizations, as well as mystical elements, such as prayer rituals and amulets of sellers.